2019
DOI: 10.1177/1351010x19863577
|View full text |Cite
|
Sign up to set email alerts
|

The use of façade sun shading systems for the reduction of indoor and outdoor sound pressure levels

Abstract: External shading devices are widely used in recent buildings because they reduce the greenhouse effect due to the solar irradiation through transparent surfaces and the glare effects in interiors. The acoustic effects of these devices have not been well investigated in the literature. In this article, we use a bi-dimensional pressure acoustics finite element model of a shading device attached to a building façade, in frequency domain, to analyse the effects both in the indoor and in the outdoor environments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The indoor-outdoor connection they provide has been, so far, a major limiting factor in the use of NV due to the conflict between ventilation needs and the intrusion of external noise, which impedes naturally ventilated buildings from meeting background noise limits set by acoustic standards, building design regulations and rating protocols. As a response, for a long time, research has been developing a number of solutions that try to guarantee ventilation without compromising façade noise insulation [19][20][21][22][23][24]. Each of them presents advantages and disadvantages, but, up to the now, none has taken hold on large scale.…”
Section: Introductionmentioning
confidence: 99%
“…The indoor-outdoor connection they provide has been, so far, a major limiting factor in the use of NV due to the conflict between ventilation needs and the intrusion of external noise, which impedes naturally ventilated buildings from meeting background noise limits set by acoustic standards, building design regulations and rating protocols. As a response, for a long time, research has been developing a number of solutions that try to guarantee ventilation without compromising façade noise insulation [19][20][21][22][23][24]. Each of them presents advantages and disadvantages, but, up to the now, none has taken hold on large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic performances have been evaluated as sound pressure level differences (Insertion Loss -IL) on building façades, between a reference scenario, without shading devices on the façade, and with various shading systems. In previous works, a standard shading system was compared to an acoustically optimised one, having louvres with sound-absorbing properties on the bottom side (Zuccherini et al, 2016) (Fausti et al, 2019) (Zuccherini et al, 2015. The conclusions of these studies are assumed in the present work.…”
Section: Introductionmentioning
confidence: 90%
“…The louvres' tilt angle was not considered in this work for daylight simulations because it was assumed that shading devices with horizontally oriented louvres constitute the best compromise between acoustic and daylight comfort: previous works have shown that louvres tilted towards sound sources can increase the sound pressure level on building façade, offering, on the other hand, the best shading to the building itself (Fausti et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate objective of investigating façade acoustics is to improve the indoor and outdoor acoustic environment. Generally, noise reduction techniques in façade acoustics include using absorptive materials, 127 134 adding control components, 135 137 applying new designs, 134,138 142 etc.…”
Section: Noise Reduction Techniquesmentioning
confidence: 99%